Sistem Informasi Akademik SMP Santa Veronika Berbasis Web - Nadia Sita; Elvira Asril (J-Com (Journal of Computer), 2022)
Abstract: The academic information system at Santa Veronika Junior High School is still  done manually. In processing academic data, it is still conventional with a data collection  system, which is now felt to have many shortcomings that occur because the existing  system still uses sheets of paper and archives so that it can cause existing data to be easily  lost or damaged. System development in the form of making a web-based academic  information system at Santa Veronika Junior High School is a system that provides online  student report information in the form of web-based student grade reports, thus helping  speed  and  quality  in  delivering  information.  In  addition,  with  a  web-based,  data  information can be accessed at an unspecified time and place. In this system, the menu  can only  be accessed by certain  users, namely admin, teacher, homeroom  teacher,  students, principal. In this study, apart from describing the theoretical study used as the  basis for the preparation, it will also discuss system design and information system  creation. System can be implemented in a product that will fix all the shortcomings that  exist in the old system. Keywords: academic; school; junior high school  Abstrak: Sistem informasi akademik pada SMP Santa Veronika masih dilakukan secara  manual. Dalam pengolahan data akademik masih secara konvensional dengan sistem  pendataan yang sekarang dirasakan masih banyak kekurangan yang terjadi dikarenakan  sistem  yang  ada  masih  menggunakan  lembaran  kertas  dan  arsip  sehingga  dapat  menyebabkan data-data yang ada mudah hilang ataupun rusak. Pengembangan sistem  berupa pembuatan sistem informasi akademik berbasis web pada SMP Santa Veronika  merupakan sistem yang memberikan informasi laporan siswa secara online yang berupa  laporan  nilai  siswa  yang  bersangkutan  dengan  berbasis  web,  sehingga  membantu  kecepatan dan kualitas dalam penyampaian informasi. Selain itu dengan berbasis web  maka informasi data dapat diakses dengan waktu dan tempat yang tidak ditentukan. Pada  sistem ini, menu hanya dapat diakses oleh user tertentu yaitu admin, guru, walikelas,  siswa,  kepala  sekolah.  Dalam  penelitian  ini  selain  memaparkan  kajian  teori  yang  digunakan sebagai dasar penyusunan, juga akan dibahas mengenai perancangan sistem  dan pembuatan sistem informasi. Hasil dari yang dibuat dapat membantu akademik dalam pendataan laporan dan memperbaiki segala kekurangan yang ada pada sistem yang lama.  Kata Kunci : akademik; sekolah; SMP